Case of Prodalmar LTDA.: To ally or not with Qingdao Bright Moon, for international expansion? - Spencer R., Erich (Estudios de Administración, 2018)
Prodalmar Ltda. (founded in Chile in 1974) is a family business owned by Mr. René Piantini, also its CEO, which is dedicated to extracting, processing and commercializing brown seaweed for foreign markets. The firm currently has 150 workers, three plants (in the cities of Antofagasta, Vallenar and Santiago), processes approximately 25,000 tons a year, bills USD 22 million annually, and its main markets are China, Japan and France. Mr. Piantini is far from comfortable in thinking that everything necessary has been done. New scenarios (a strong and growing demand and above all increased competition) and the limitation of his own resources, which are typical of an SME like his, have led him to seriously consider increasing his production capacity and enhance his international marketing efforts by developing a strategic alliance with a foreign partner. Generally speaking, his main option is a Chinese company named Qingdao Bright Moon Seaweed, with whom Prodalmar has been jointly handling the distribution of its products in China for more than 15 years, developing very good relationships at both the business and personal level. Nonetheless, Mr. Piantini is quite clear that this is not an easy decision and although he is seriously considering the possibility of establishing this strategic alliance with a foreign partner, there are several questions that he has to address beforehand: Is it really convenient for Prodalmar to undertake a strategic alliance with Bright Moon? How will the company’s current relationship with Bright Moon change after starting a joint venture, which will in fact mean the creation of a new firm ownership and control are shared? What would happen if in the near future the current positive conditions of the market are not so prosperous? In addition to the intrinsic complexity of the decision to be made, it is important to add that during the second semester of 2012, another foreign investor had offered Mr. Piantini a significant amount of money to acquire his company.